DOES FISCAL DECENTRALIZATION AFFECT ON THE CONVERGENCE OF PER CAPITA INCOME IN INDONESIA? - Negara, Bonnie Permana; Khoirunurrofik, Khoirunurrofik (Politeknik Keuangan Negara STAN, 2020)
Nearly two decades since 2001 Indonesia has implemented a decentralized system. The basis of decentralization implemented in Indonesia is at the regency/municipality level while fiscal decentralization is carried out fully in the area of expenditure. It is important to know whether the implementation of fiscal decentralization has an effect on national development. One indicator to determine the impact of fiscal decentralization on development is whether there is economic convergence between regions during the period of regional autonomy. Using panel data of 411 regencies and 94 municipalities in Indonesia during the implementation period of decentralization from 2001-2017, this study aims to examine indications of economic convergence between regions in Indonesia. This study uses indicators of fiscal decentralization in terms of expenditure assignment, namely regional spending on education, health, and infrastructure. Based on the test results of both static convergence and dynamic convergence testing, it was found that there was a convergence of per capita income between regency/municipality in Indonesia.